THE EFFECT OF SCHOOL WELL-BEING ON GRIT WITH THE GROWTH MINDSET AS MEDIATOR - Ida Saidah; Asmadi Alsa; Anizar Rahayu (Dinasti International Journal of Education Management And Social Science, 2021)
The character of grit is to emphasize the importance of desire, interest so that students can achieve the desired achievements when students have resilience and persistence. There are still many schools that have learning targets that emphasize the value of achievement rather than character building. As the result, it can be found the phenomenon of students who are not enthusiastic to maintain interest, do not have the resilience to overcome obstacles and challenges, and have a need for achievement with an unyielding mentality. The purpose of this study is to examine the theoretical model of the effect of school well-being on grit with a growth mindset as a mediator. Three hundred and thirteen school-age students were surveyed. The research instrument used in this study is a questionnaire based on a Likert scale model and being tested through several stages to obtain valid and reliable instrument. The finding suggests that theoretical model fits with the empirical data. However, contrary to expectations, results from SEM analyses indicates that growth mindset has no positive and significant effect in mediating influence of school well-being on grit of students from 10 Integrated Islamic Elementary Schools in four sub-districts of Bekasi Regency. Rather, results show two direct effects; that growth mindset and grit go hand in hand and that school well-being supportd growth mindset. Gender differences are observed in growth mindset and school well-being. Theoretical and practical implications for parents and teachers are also discussed.